Behavioral responses to spatial heterogeneity in endangered Ganges River dolphins (Platanista gangetica gangetica) - Shambhu Paudel; John L. Koprowski; Usha Thakuri; Yukiko Sasaki-Yamamoto; Shiro Kohshima (Water Biology and Security, 2022)
Globally, the threat of endangerment and extinction of small cetaceans was highlighted after the recent extinction of the Chinese River dolphin or Baiji (Lipotes vexillifer). Species with a small population size and a limited geographic range, such as Ganges River dolphins (GRD), are more vulnerable to extinction. The social and behavioral needs of cetaceans have been identified as potential factors increasing their vulnerability to human disturbance. However, little is known about how GRD adapt their behaviors and diel activity patterns to spatiotemporal variation. In this paper, we examined the underwater behavior of GRDs in Nepal by collecting echolocation clicks from three spatially stratified habitats in the Sapta Koshi River system over a six-month period. Our research found that GRDs behave differently in response to spatial heterogeneity, indicating diverse environmental requirements for GRD persistence. Behavioral activity and duration varied across habitats but not across time of day, suggesting that GRD behaviors are likely to be regulated by habitat structure regardless of the time of day. However, GRD consistently exhibited nocturnal activity peaks even when diurnal activity varied substantially. This indicates that river dolphins may favor nocturnal refuges as a reaction to human disturbance in highly regulated rivers. Managing human disturbances in conjunction with habitat heterogeneity can improve the persistence of riverine cetaceans. Here, we document behavioral and ecological information pertaining to GRD, which is essential to the formation of river dolphin recovery plans that link ecological perspectives to planning and management.